Desain Bahan Ajar Keterampilan Membaca pada Program Ta’lim Idhafi di STAI Darul Ulum Banyuanyar Pamekasan - Hamdy, Mohammad Zainal (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
The Ta'lim Idhafi program is the flagship of STAI Darul Ulum Banyuanyar Pamekasan in starting educational programs. Where the material used at the start of this program was felt to not be appropriate to the needs of students so a redesign of the material needed to be carried out. This research uses research and development, in designing teaching materials researchers use the Borg and Gall theory. The results of this research are that the Design of Reading Skills Teaching Materials in the Ta'lim Idhafi Program at STAI Darul Ulum Banyuanyar Pamekasan is suitable for use according to the validation of 2 experts with several notes and revisions.